Employee Anonymous Online Dissent: Dynamics and Ethical Challenges for Employees, Targeted Organisations, Online Outlets, and Audiences - Ravazzani, Silvia (Business ethics quarterly, 2018)
This article aims to enhance understanding of employee anonymous online dissent (EAOD), a controversial phenomenon in contemporary digital environments. We conceptualise and scrutinise EAOD as a communicative and interactional process among four key actors: dissenting employees, online outlet administrators, audiences, and targeted organisations. This multi-actor, dialectical process encompasses actor-related tensions that may generate unethical consequences if single voices are not brought out and confronted. Appropriating a Habermasian ethical and discursive lens, we examine and disentangle three particular challenges emerging from the EAOD process: lack of accountability and potential opportunism; equal participation and resolution of actor-related tensions; and organisational participation and internalisation of dissent. We show that EAOD can initiate plural dialogue that helps co-construct and balance different voices within an informal and noninstitutionalised context for interaction and public deliberation. We conclude our inquiry by offering reflections on practical implications and a research agenda for further investigation.